Ore Image Classification Based on Improved CNN. (April 2022) - Zhou, Wenyan; Wang, Hao; Wan, Zhibo
Abstract: The identification of ore deposits is an important technical task in mining and excavation. However, conventional techniques are time-consuming and tedious. Therefore, data augmentation and transfer learning were used in this topic to improve the classification accuracy of ore deposit datasets. The model was pre-trained using 957 images of seven different ore types, which were acquired from a Public Kaggle dataset. Five different convolutional neural network (CNN) models were selected for weight acquisition, including AlexNet, VGG16, ResNet50, InceptionV3, and MobileNet. The comparative experiments demonstrated the use of transfer learning to be effective against improving classification performance, such as reaching 94% with the MobileNet model. The classification performance was further improved by training a Squeeze-and-Excitation Networks (SENet) classifier using features calculated with MobileNet, resulting in an accuracy of 96%. These results prove that the proposed technique, which combines a CNN with transfer learning, data augmentation, and SENet, to be an effective new tool for automated ore classification, offering higher accuracy with less training data.